2016
DOI: 10.1248/cpb.c15-00828
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Hybridization of Vizantin and Lipid A to Generate a Novel LPS Antagonist

Abstract: Gram-negative sepsis and septic shock are serious conditions caused by the release of bacterial endotoxin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
(29 reference statements)
0
5
0
1
Order By: Relevance
“…In a recent study, it was shown that the trehalose derivative named Vizantin (6,6 -bis-O-(3-nonyldodecanoyl)α,α -trehalose) displays adjuvant activity based on TLR4 agonism and binding to the TLR4/MD-2 complex. Based on the known biological activity of lipid A and Vizantin, the authors projected a novel bifunctional glycolipid, that combines the structural features of Vizantin (namely, the two branched FA chains 3-nonyldodecanoic acid, 3NDDA) with the glucosamine core of lipid A (compound 4; Figure 1) [45]. Disaccharide 4 potently antagonizes the LPS/TLR4 signaling pathway in a concentration-dependent manner, in human THP-1 cells, with an IC 50 of 3.8 nM.…”
Section: Lipid a Mimetic With Vizantin-like Branched Chainsmentioning
confidence: 99%
“…In a recent study, it was shown that the trehalose derivative named Vizantin (6,6 -bis-O-(3-nonyldodecanoyl)α,α -trehalose) displays adjuvant activity based on TLR4 agonism and binding to the TLR4/MD-2 complex. Based on the known biological activity of lipid A and Vizantin, the authors projected a novel bifunctional glycolipid, that combines the structural features of Vizantin (namely, the two branched FA chains 3-nonyldodecanoic acid, 3NDDA) with the glucosamine core of lipid A (compound 4; Figure 1) [45]. Disaccharide 4 potently antagonizes the LPS/TLR4 signaling pathway in a concentration-dependent manner, in human THP-1 cells, with an IC 50 of 3.8 nM.…”
Section: Lipid a Mimetic With Vizantin-like Branched Chainsmentioning
confidence: 99%
“…proinfl amatorios efectores de la respuesta inmune inducida por los gram negativos en la sepsis. Un mecanismo idéntico como antagonista del lipopolisacárido se ha descrito y probado en modelos animales para el quercetín, principal fl avonoide de las plantas y uno de los principales constituyentes de la dieta humana presente en frutas, verduras y bebidas (16)(17)(18)(19).…”
Section: Tipounclassified
“…Because septic shock and/or Gram-negative sepsis are fatal in approximately 30-40% of patients, TLR antagonists for LPS have thus far attracted considerable interest as potential treatments for these methods of sepsis. [13][14][15][16] Recently, we have developed vizantin (1), 17,18) 6,6′-bis-O-(3nonyldodecanoyl)-α,α′-trehalose, as a safe immunostimulator on the basis of a structure-activity relationship study with trehalose 6,6′-dicorynomycolate (TDCM) (2) [19][20][21][22][23][24] that was first characterized as a structural component of the outer surface membrane of Corynebacterium diphtheriae (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%